2017
DOI: 10.1002/cnma.201700252
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Functionalized Nanoparticles of Semiconducting Metal Chalcogenides and Their Attributes

Abstract: Covalent functionalization of the semiconducting chalcogenide nanoparticles ZnS, ZnSea nd CdS by reaction with organic halides, specifically iodobenzenes, has been demonstrated. DFT calculations have thrown light on the electronic structure of the functionalized chalcogenides. Chalcogenides with bonded phenyl groups exhibit al ong wavelength charge-transfer band as predicted by theory.F unctionalization has been carried out with fluorophores as well. Functionalization of semiconductingc halcogenide particles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Figure S2 shows that the coverage of methyl-functionalized ceMoS 2 (methyl-MoS 2 ) was the same whether water/ isopropanol 18 or DMF was used as the solvent. Although palladium catalysts have been used to functionalize 2H-MoS 2 and metal chalcogenide nanoparticles with iodobenzene, 41,44 we have observed that functionalization of 2H-MoS 2 using one-electron metallocenes does not proceed as readily as for 1T′-MoS 2 . The details of how the strength of the metallocene reductant affects the functionalization of 2H-MoS 2 remains an area of active interest.…”
mentioning
confidence: 99%
“…Figure S2 shows that the coverage of methyl-functionalized ceMoS 2 (methyl-MoS 2 ) was the same whether water/ isopropanol 18 or DMF was used as the solvent. Although palladium catalysts have been used to functionalize 2H-MoS 2 and metal chalcogenide nanoparticles with iodobenzene, 41,44 we have observed that functionalization of 2H-MoS 2 using one-electron metallocenes does not proceed as readily as for 1T′-MoS 2 . The details of how the strength of the metallocene reductant affects the functionalization of 2H-MoS 2 remains an area of active interest.…”
mentioning
confidence: 99%
“…Chemical functionalization is a promising route to tune chemical and physical properties, improve processability as well as to develop novel structures . Abellán et al .…”
Section: Synthesis Structure and Propertymentioning
confidence: 99%